Factors Affecting the Service Efficiency of International Freight Forwarding Companies - Ayasanond, Chitpong; Munkongtum, Chutidaj; Thriyawanich, Chalita (Interdisciplinary Academic and Research Journal, 2024)
Background and Aims: This research aims to explore factors influencing the efficiency of international freight forwarding companies, in responding to rapidly changing market demands. The main objectives are 1) to study opinions on factors affecting company efficiency, and 2) to analyze the relationship between information systems, service networks, and customer relationship management with service efficiency in international freight forwarding businesses. The goal is to assist companies in this industry to improve and develop operational strategies for enhanced efficiency. Methodology: This quantitative research conducted surveys using questionnaires to analyze the relationship between various factors and the service efficiency of international freight forwarding companies. A purposive sampling of 385 participants was used, collecting data via Google Forms distributed through online networks. The IOC value was 0.67, and Cronbach’s Alpha was 0.72. Descriptive statistics were used to explore demographic characteristics and assess the importance of service factors, utilizing means and standard deviations for summarizing basic data. Inferential statistics focused on correlation analysis, employing correlation coefficients and P-values to examine relationships and statistical significance, affirming the role of information systems, service networks, and customer relationship management in service efficiency. Results: The study found that (1) the general demographic of the 385 respondents was predominantly male, aged 21-30, at officer level, in the service industry sector, belonging to large-sized organizations, and involved in more than 15 import-export transactions per month; (2) significant factors for the service efficiency of international freight forwarding companies included information systems, service networks, and customer relationship management, all highly important for service efficiency; (3) information systems, service networks, and customer relationship management positively correlated with enhancing service efficiency. Conclusion: The research indicates that key factors in the business of international freight forwarding companies, such as information systems, service networks, and customer relationship management, have a positive relationship with company service efficiency.